CLINICAL-NEUROLOGICAL PECULIARITIES OF VERTEBROGENIC RADICULOPATHS IN THE DYNAMICS OF MICRODISCECTOMY - Maksudova, Hurshida Nabiyevna; Ergasheva, Nargiza Obidjanovna; Ubaydullaeva, Sarbi Isakbaevna (Медицина: теория и практика, 2020)
Among the lesions of the spine, one of the most common is osteochondrosis, which is a degenerative-dystrophic changes in the intervertebral disc and bone-ligamentous apparatus.